(untitled) (World Bulletin of Public Health, 2023)
Today, the unsatisfactory results of organ-preserving surgical interventions for a malignant tumor of the rectal ampulla depend on the morphological characteristics of the cancer; indications for organ-preserving operations are substantiated based on the level of the morphological structure of the rectalampulla part of the cancer.